Loss of AZIN2 splice variant facilitates endogenous cardiac regeneration. Issue 12 (6th April 2018) - Li, Xinzhong; He, Xiang; Wang, He; Li, Mengsha; Huang, Senlin; Chen, Guojun; Jing, Yuanwen; Wang, Shifei; Chen, Yanmei; Liao, Wangjun; Liao, Yulin; Bin, Jianping
Abstract: Aims: Long noncoding RNAs (lncRNAs) are critical regulators of cardiovascular lineage commitment and heart wall development, but their roles in regulating endogenous cardiac regeneration are unclear. The present study investigated the role of human-derived lncRNA in regulating endogenous cardiac regeneration as well as the underlying mechanisms. Methods and results: We compared RNA sequencing data from human foetal and adult hearts and identified a novel lncRNA that was upregulated in adult hearts (Genesymbol NONHSAG000971/NONHSAT002258 or ENST00000497710.5), which was a splice variant of the AZIN2 gene (AZIN2-sv). We used quantitative PCR to confirm the increased expression of AZIN2-sv in adult rat hearts. Coexpression network analysis indicated that AZIN2-sv could regulate proliferation. Loss- and gain-of-function approaches demonstrated that AZIN2-sv negatively regulated endogenous cardiomyocyte proliferation in vitro and in vivo. Knockdown of AZIN2-sv attenuated ventricular remodelling and improved cardiac function after myocardial infarction. Phosphatase and tensin homolog (PTEN) was identified as a target of AZIN2-sv, their direct binding increased PTEN stability. Furthermore, AZIN2-sv acted as a microRNA-214 sponge to release PTEN, which blocked activation of the PI3 kinase/Akt pathway to inhibit cardiomyocyte proliferation. Conclusions: The newly discovered AZIN2-sv suppressed endogenous cardiac regeneration by targeting the PTEN/Akt pathway. Thus, AZIN2-sv may be a novel therapeutic target for preventing and treating heart failure.